Canal Transportation and Centering Ability of Reciproc Blue, WaveOne Gold and ProTaper Next in Simulated Curved Canals - Silva, Priscila Florentino; Coelho, Esio; Alves, Nayane Chagas Carvalho; Silva, Silmara Andrade; Pereira, FÃ¡bio Cavalcanti; Albuquerque, Diana Santana (Iranian Endodontic Journal, 2018)
Introduction: The aim of this study was to evaluate the canal transportation and centering ability of ProTaper Next (PTN), WaveOne Gold (WOG) and Reciproc Blue (RCB) in simulated curved resin canals. Methods and Materials: A total of 43 blocks of simulated resin canals with 40° of curvature were prepared to an apical size of 0.02. Flexofile #15 instruments were used along the root canal to reach patency. The blocks were randomly assessed and sequence instruments were used according to each system: PTN, RCB and WOG. The imposition of pre and post instrumentation images were composited and analyzed. The canal transportation and apical centralization were measured using the software GIMP (2.8.4, Creative Commons - Share Alike 4.0 International License, 2013). Data were statistically analyzed using the Shapiro-Wilk test, ANOVA test and Tukey's test. The level of significance was set at 0.05. Results: There were no statistical differences in canal transportation between three systems. The general assessment of three systems presented the RCB group with higher values of centralization and more numbers of centralized points with significant differences between the PTN and RCB groups (P<0.05). Conclusion: In this in vitro study, there were no statistical differences in canal transportation between the RCB, WOG and PTN systems. The lowest transportation was observed in the apical region at 3 mm performed with RCB system, followed by WOG and PTN systems. The RCB demonstrated higher values of centralization and more centralized points when assessed by regions.